Proteomic Responses to Alkali Stress in Oats and the Alleviatory Effects of Exogenous Spermine Application - Bai, Jianhui; Jin, Ke; Qin, Wei; Wang, Yuqing; Yin, Qiang (Frontiers in Plant Science, 2021)
Alkali stress limits plant growth and yield more strongly than salt stress and can lead to the appearance of yellow leaves, but the reasons remain unclear. In this study, we found that 1) the down-regulation of Coproporphyrinogen III oxidase, Protoporphyrinogen oxidase, and Pheophorbide a oxygenase in oats under alkali stress contributes to the appearance of yellow leaves using the proteome analysis and western blot analysis. 2) Some oat proteins that are involved in the antioxidant system, root growth, and jasmonic acid (JA) and indole-3-acetic acid (IAA) synthesis are up-regulated in response to alkalinity and help increase alkali tolerance. 3)We added exogenous spermine to improve alkali tolerance, and oats treated with exogenous spermine had higher chlorophyll contents and plant fresh weights than plants subject to alkalinity due to up-regulation of Chitinase and proteins related to chloroplast structure, root growth, and the antioxidant system. Spermine addition increased sucrose utilization efficiency, and promoted carbohydrate export from leaves to roots to increase energy storage in roots. Spermine addition also increased the IAA and JA contents required for root growth.